The Ethics of Genetic Research of Intelligence - Reiss, Michael J. (Bioethics, 2000)
Should research on the possible genetic components of human intelligence be carried out? I first try to provide some general guidelines as to whether any particular piece of research should be undertaken and then consider the specific example of the ethics of genetic research on intelligence. The history of the debate on intelligence does not make one very optimistic that the fruits of such research would be used wisely. However, there are indications that people’s understanding of the nature of inheritance may be improving and it could be that such research might have significant benefits. It is worth remembering than the condition phenylketonuria, a genetic disease in any useful sense of the term, and one that leads to mental retardation (i.e. very low intelligence), is now wholly preventable, and indeed very largely prevented, through environmental intervention.